2023
DOI: 10.1093/mnras/stad1551
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the Galactic thin and thick discs, their abundance gradients and the diagnostic potential of their abundance ratios

Abstract: Using a semi-analytical model of the evolution of the Milky Way, we show how secular evolution can create distinct overdensities in the phase space of various properties (e.g. age vs metallicity or abundance ratios vs age) corresponding to the thin and thick discs. In particular, we show how key properties of the Solar vicinity can be obtained by secular evolution, with no need for external or special events, like galaxy mergers or paucity in star formation. This concerns the long established double-branch beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…Indeed, the efficiency of the s-process in low-mass stars is known to increase with metallicity and go through a maximum at a value that depends on the mass number of the isotope: the production of heavier isotopes reaches that maximum at lower metallicity values than lighter ones (see, e.g., Figure 1 in Travaglio et al 2004). For that reason, the evolution of the [s-/Fe] ratio of elements of the second s-peak, like Ba or Ce, is expected to display a small bump at slightly subsolar metallicities, as found in Figure 5 of Travaglio et al (2004), Figure 2 of Grisoni et al 2020, or in Prantzos et al (2018 for one-zone models (their Figure 16) and Prantzos et al (2023;their Figure 14), which adopt different sets of yields (see the discussion in the first paragraph of Section 5).…”
Section: [Ce/fe]-[fe/h] Planementioning
confidence: 79%
“…Indeed, the efficiency of the s-process in low-mass stars is known to increase with metallicity and go through a maximum at a value that depends on the mass number of the isotope: the production of heavier isotopes reaches that maximum at lower metallicity values than lighter ones (see, e.g., Figure 1 in Travaglio et al 2004). For that reason, the evolution of the [s-/Fe] ratio of elements of the second s-peak, like Ba or Ce, is expected to display a small bump at slightly subsolar metallicities, as found in Figure 5 of Travaglio et al (2004), Figure 2 of Grisoni et al 2020, or in Prantzos et al (2018 for one-zone models (their Figure 16) and Prantzos et al (2023;their Figure 14), which adopt different sets of yields (see the discussion in the first paragraph of Section 5).…”
Section: [Ce/fe]-[fe/h] Planementioning
confidence: 79%
“…Thorsbro et al (2020), Feldmeier-Krause (2022), and Nogueras-Lara et al (2023), for example, by analyzing quite a large number of giants in the Galactic center, have shown that the metallicities of these stars reaches up to 10 times the solar metallicity. Therefore, the use of stellar yields from SSM sources is essential to study the formation and the chemical evolution of these regions (Cinquegrana & Karakas 2022;Prantzos et al 2023). Furthermore, we note that the yields we present in this paper have already been adopted by Prantzos et al (2023).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the use of stellar yields from SSM sources is essential to study the formation and the chemical evolution of these regions (Cinquegrana & Karakas 2022;Prantzos et al 2023). Furthermore, we note that the yields we present in this paper have already been adopted by Prantzos et al (2023).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations